Effects of arecoline on cell growth, migration, and differentiation in cementoblasts - Yi-Juai Chen; Shiuan-Shinn Lee; Fu-Mei Huang; Hui-Chieh Yu; Chi-Cheng Tsai; Yu-Chao Chang (Elsevier, 2015)
Background/purpose: Studies have supported a higher prevalence of periodontal disease among areca quid chewers than non-chewers. However, few studies have stated the effects of areca quid on periodontal tissues. The aim of this study was to investigate the inhibitory effects of arecoline, the major alkaloid of areca nut, on murine immortalized cementoblast cell line (OCCM.30). Materials and methods: Cytotoxicity was judged using tetrazolium bromide reduction assay. Cell migration was evaluated by Transwell assay. In vitro mineral nodule formation was assayed by von Kossa staining. Cell differentiation was examined by alkaline phosphatase activity with substrate assay. The production of osteoprotegerin was evaluated using enzyme-linked immunosorbent assay. Results: Arecoline demonstrated cytotoxicity to cementoblasts in a dose-dependent and time-dependent manner (P < 0.05). Arecoline attenuated cell migration in a dose-dependent manner (P < 0.05). Arecoline treatment markedly suppressed cementoblast-mediated biomineralization in vitro compared to untreated cells at Day 8. Arecoline was found to inhibit alkaline phosphatase activity in a time-dependent manner (P < 0.05). In addition, arecoline decreased the secretion of osteoprotegerin in a dose-dependent manner (P < 0.05). Conclusion: Taken together, these results suggest that arecoline could inhibit cell growth, migration, and differentiation in cementoblasts. Areca quid chewers might be more susceptible to the destruction of periodontium and less responsive to regenerative procedure during periodontal therapy.